Warfare in late Byzantium, 1204-1453 - Kyriakidis, Savvas (History of warfare ;, 2011)
"This book examines Byzantine attitudes towards warfare at a time of crisis when the empire ceased to be a first rate power in the Mediterranean. It investigates the correspondence between official rhetoric and propaganda, on the one hand, and military realities, on the other. It explores the military ethos of the late Byzantine aristocracy and examines Byzantine perceptions of military leadership in comparison to contemporary western European military thinking. The organization and nature of military operations and the role of the various groups of soldiers are explored to set Byzantine warfare in the wider geographical and cultural context. In addition, this book provides a comprehensive analysis of the influences other medieval cultures exerted on Byzantine military thought, organization and practice"--Page 4 of cover